Analysis of Brand Image and Online Consumer Reviews on Consumer Loyalty - Lisnawati Lisnawati Lisnawati; Asep Muhamad Ramdan; Dicky Jhoansyah Jhoansyah (Faculty of Economics and Business, Universitas Malikussaleh, 2021)
This study aims to determine the effect of the brand image variable (X1) and online consumer review on consumer loyalty (Y). The method used in this research is descriptive and associative methods using a quantitative approach, the sample used is 150 respondents to consumers of Nature Republic Aloe Vera 92% Soothing Gel in Sukabumi City which are distributed using googlefrom, and using probability sampling techniques using probability sampling. random sampling. The data analysis technique used is the multiple linear analysis technique, the T test and the F test. The results of this study indicate that the brand image variable (X1) has a positive and significant effect on the consumer loyalty variable (Y) and the online consumer review variable (X2) also has a positive and significant effect on the consumer loyalty variable (Y). The coefficient of determination test results showed a value of 0.516 which can be interpreted as the percentage of variables X1 and X2 which have a value of 51.6% and the remaining 48.4% which is influenced by other factors not examined in this study.